Assessing the social dynamics of Minas Gerais municipalities created after the Federal Constitution of 1988 (Revista Espinhaço, 2019)
Since the approval of the Federal Constitution of 1988 in Brazil, there are a district emancipationist race within most of states. In Minas Gerais state, 130 municipalities were created between 1988 and 2019. In order to measure the degree of success of district emancipations in Minas Gerais and the possible social achievements, this research used the Índice Mineiro de Minas Gerais Social Responsibility Index for the years 2000, 2010 and 2016, we calculated the variation of this index growth of each municipality between 2000-2010 and 2000-2016. Using descriptive statistic, we observed that the dimension “health” presents a significant impact on IMRS increase among the municipalities analyzed.
Keywords: district emancipations; municipalities of Minas Gerais; social development; IMRS